Evaluation of the effects of kidney function tests on prognosis and mortality in geriatric patients with a pulmonary embolism - Hatice Şeyma Akça; Serdar Özdemir; Abuzer Özkan; Serkan Küçüktürk; Fulya Köse (National Scientific Medical Center, 2022)
Aim: The instant study's aim is to investigate the effect that BUN and creatinine values have on a prognosis in geriatric patients that are diagnosed with pulmonary embolism. Material and methods: Our study was planned as a retrospective data review and included patients over the age of 65 with a diagnosis of pulmonary embolism who were admitted applied to Ümraniye Training and Research Hospital between March 1, 2020, and March 1, 2022. Statistical analysis was performed using SPSS version 26.0. Results: The study included 148 patients, and 66.89% of them were women. The mortality rate was 28.38%. Considering the blood gas parameters, there was a statistically significant relationship between PH and low saturation and mortality (p=0.029, p=0.001, respectively). Although creatinine values were higher in non-surviving patients than in surviving patients, it was not statistically significant (p=0.252). Blood urea nitrogen was statistically significantly higher in patients who died (p=0.001). Sodium and potassium values were also not associated with mortality (p=0.991, p=0.886, respectively). Conclusion: The effect of kidney function tests on the prognosis is very important in managing pulmonary embolism. BUN will be more beneficial to the clinician than creatinine and plasma electrolytes in the management of patients with pulmonary embolism.